2001
DOI: 10.1139/cjpp-79-9-779
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting independent sodium-sensitive and sodium-insensitive mechanisms of genetic hypertension in spontaneously hypertensive rats (SHR)

Abstract: Some essential hypertensive patients and genetic hypertensive rat strains have less than the normal levels of Mg2+ tightly bound to the plasma membranes of their erythrocytes and other cells, i.e., the magnesium binding defect (MgBD). This binding defect appears to cause increased passive permeability of the membrane to Na+ and thereby its increased intracellular concentration, particularly if the Na+-extrusion enzyme systems of the cell are also defective. The Na+-Ca2+ exchange system in the cell membrane exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Further, the intracellular magnesium ion concentration in these studies correlated significantly and inversely with the average blood pressure of the subjects involved. This result suggested a possible causal relationship, which was later confirmed (Wells and Blotcky 2001), between the decreased intracellular concentration of magnesium ions and Na + -sensitive essential hypertension.…”
Section: Magnesium-binding Defect (Mgbd)supporting
confidence: 50%
“…Further, the intracellular magnesium ion concentration in these studies correlated significantly and inversely with the average blood pressure of the subjects involved. This result suggested a possible causal relationship, which was later confirmed (Wells and Blotcky 2001), between the decreased intracellular concentration of magnesium ions and Na + -sensitive essential hypertension.…”
Section: Magnesium-binding Defect (Mgbd)supporting
confidence: 50%
“…[23][24][25][26][27] Consistent with the established importance of NCX1 in systemic vascular SMCs, a number of studies have shown that the hypertension is associated with changes in the activity of NCX in various types of arterial beds. [28][29][30][31][32][33][34] Using the specific inhibitor of Ca 2+ entry through NCX1 SEA0400, NCX1-deficient mice, and transgenic mice that specifically express NCX1.3 in smooth muscle, Iwamoto et al have recently demonstrated that salt-sensitive hypertension is triggered by Ca 2+ entry through NCX1 in arterial smooth muscle. 35 Pulmonary circulation is structurally and functionally different from systemic circulation at the regional tissue, cellular, and molecular levels.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Dysregulation of [Ca 2ϩ ] i can lead or contribute to deleterious pathogenic conditions, including neurodegenerative diseases 7 and salt-sensitive hypertension. 1,8 Recently, there has also been a preponderance of evidence implicating oxidative stress in the pathogenesis of hypertension, 9,10 and this effect of oxidative stress might occur, at least in part, through alterations in [Ca 2ϩ ] i dynamics. Because the NCX is 1 of the primary regulators of [Ca 2ϩ ] i , alterations in [Ca 2ϩ ] i dynamics under oxidative stress conditions might be attributed, at least to some extent, to dysregulation of the NCX.…”
mentioning
confidence: 99%